Specific subpopulations of hypothalamic leptin receptor-expressing neurons mediate the effects of early developmental leptin receptor deletion on energy balance - Alan C. Rupp; Margaret B. Allison; Justin C. Jones; Christa M. Patterson; Chelsea L. Faber; Nadejda Bozadjieva; Lora K. Heisler; Randy J. Seeley; David P. Olson; Martin G. Myers, Jr (Elsevier, 2018)
Objective: To date, early developmental ablation of leptin receptor (LepRb) expression from circumscribed populations of hypothalamic neurons (e.g., arcuate nucleus (ARC) Pomc- or Agrp-expressing cells) has only minimally affected energy balance. In contrast, removal of LepRb from at least two large populations (expressing vGat or Nos1) spanning multiple hypothalamic regions produced profound obesity and metabolic dysfunction. Thus, we tested the notion that the total number of leptin-responsive hypothalamic neurons (rather than specific subsets of cells with a particular molecular or anatomical signature) subjected to early LepRb deletion might determine energy balance. Methods: We generated new mouse lines deleted for LepRb in ARC GhrhCre neurons or in Htr2cCre neurons (representing roughly half of all hypothalamic LepRb neurons, distributed across many nuclei). We compared the phenotypes of these mice to previously-reported models lacking LepRb in Pomc, Agrp, vGat or Nos1 cells. Results: The early developmental deletion of LepRb from vGat or Nos1 neurons produced dramatic obesity, but deletion of LepRb from Pomc, Agrp, Ghrh, or Htr2c neurons minimally altered energy balance. Conclusions: Although early developmental deletion of LepRb from known populations of ARC neurons fails to substantially alter body weight, the minimal phenotype of mice lacking LepRb in Htr2c cells suggests that the phenotype that results from early developmental LepRb deficiency depends not simply upon the total number of leptin-responsive hypothalamic LepRb cells. Rather, specific populations of LepRb neurons must play particularly important roles in body energy homeostasis; these as yet unidentified LepRb cells likely reside in the DMH. Keywords: leptin receptor, arcuate nucleus, DMH, obesity, cre recombinase, ghrh, htr2c